Antioxidant, anti-inflannnatory and anti-pyretic activities of trichosanthes dioica roxb. fruits - Alam, M. Badrul; Hossain, M. Sarowar; Chowdhury, N. Sultana; Asadujjaman, M.; Zahan, Ronok; Islam, M. Monirul; Mazumder, M. Ehsanul Haque; Haque, M. Ekramul; Islam, Anwarul (© 2011 Academic Journals Inc., 2016)
This article was published in Journal of Pharmacology and Toxicology [© 2011 Academic Journals Inc.] and the definite version is available at: https://goo.gl/yQ4Sfd